Tool interference at workpiece centre in single-point diamond turning. (February 2019) - Zhang, Guoqing; Dai, Yuqi; To, Suet; Wu, Xiaoyu; Lou, Yan
Highlights: Center error and it induced tool interference have a close relation to cutting force peaks. Tool elevation has a threshold, beyond which diamond tool can be elevated and forms a round highland. Depth of cut, center error, tool nose radius and tool clearance angle have effects on tool interference zone. A mathematical model was derived to calculate the tool interference position and scope. Abstract: In single-point diamond turning (SPDT), the workpiece centre error owing to the tool height below or above the spindle axis causes cylinder or cone appearances at the workpiece centre. The formed cone or cylinder boundary is used to identify the tool height and then compensate for it, in order to obtain the desired surface profile. As opposed to previous studies, based on the fact that the diamond tool is elevated during cone formation and therefore forms a tool interference zone with higher land and larger radius, this research conducts a theoretical and experimental study to investigate the origin of tool interference owing to centre error, and its influencing factors. In this study, the relation between centre error and interference force was investigated. A series of experiments were conducted to explore tool interference generation and its influencing factors. A mathematical model was derived to calculate the tool interference zone radius, whereby the relation between this radius and the cutting conditions was established. Moreover, the error sources between the theoretical and experimental results were analysed. As centre error can only be reduced by compensation and cannot be eliminated, particularly in machine tools with poor resolution, it is meaningful to conduct research on the centre cone generation and its influence on tool interference in SPDT, as well as suppressing the tool interference in SPDT. Furthermore, this research provides a reference for establishing an online force-based centre error identification method, thereby improving cutting efficiency. Graphical abstract: